A Prospective Pilot Investigation of Brain Volume, White Matter Hyperintensities, and Hemorrhagic Lesions after Mild Traumatic Brain Injury - Jarrett, Michael; Tam, Roger; Hernández-Torres, Enedino; Martin, Nancy; Perera, Warren; Zhao, Yinshan; Shahinfard, Elham; Dadachanji, Shiroy; Taunton, Jack; Li, David K. B.; Rauscher, Alexander (Frontiers in Neurology, 2016)
Traumatic brain injury (TBI) is among the most common neurological disorders. Haemorrhagic lesions and white matter hyperintensities (WMH) are radiological features associated with moderate and severe traumatic brain injury TBI. Brain volume reductions have also been observed during the months following injury. In concussion, no signs of injury are observed on conventional MRI, which may be a true feature of concussion or merely due to the limited sensitivity of imaging techniques used so far. Moreover, it is not known whether volume reductions are due to the resolution of trauma related edema or a true volume loss. Forty five collegiate level ice hockey players (20 female) and 15 controls (9 female) 40 players underwent 3T MRI for haemorrhages (multi echo susceptibility weighted imaging (SWI)), WMH (three dimensional FLAIR) and brain volume at the beginning and the end of the hockey season. Concussed athletes underwent additional imaging and neuropsychological testing at three days, two weeks, and two months after injury. At the end of the hockey season, brain volume was reduced compared to controls by 0.32% (p<0.034) in the whole cohort and by 0.26% (p<0.09) in the concussed athletes. Two weeks and two months after concussion, brain volume was reduced by -0.08% (p=0.027) and -0.23% (p=0.035), respectively. In athletes, the WMH were significantly closer to the interface between grey matter and white matter compared to controls. No significant changes in the number of WMH over the duration of the study were found in athletes. No microhaemorrhages were detected as a result of concussion or playing a season of ice hockey. We conclude that mild TBI does not lead to transient increases in brain volume and no new microbleeds or WMH are detectable after concussion. Brain volume reductions appear by two weeks after concussion and persist until at least two months after concussion. Brain volume is reduced between the beginning and the end of the ice hockey season.